The Impact of Armed Conflict on Children Health : Systematic Literature Review - mona ulli hidayati; Salahudin Salahudin; Syamsul Rizal; M. Syaprin Zahidi (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
This study examines what armed conflict is for children and how to resolve it. It aims to develop where it affects early childhood in various countries disclosing the adverse consequences of armed conflict on health outcomes for children under five. Especially those who are exposed to the conflict. Although recent evidence suggests a significant and long-lasting detrimental effect of armed conflict on children's health, there needs to be more assessment of the effectiveness of various social and economic development interventions aimed at reducing the impact of armed conflict on children's health. The research method applied in this research is a systematic literature review using 113 scientific articles sourced from the Scopus database. Review articles using the Vosviewer application. the results of this study yield on the challenges faced by conflict-affected countries. Social funds, one of the main instruments used to promote development at the local level, can be used to reduce the impact of armed conflict on children's health and the role of UNICEF in helping the mental healing of these children. For children living in displaced households, specific interventions should be designed to reduce the impact of armed conflict. The articles used are only sourced from database coverage, so research findings cannot be comprehensively described on the issue of child health due to the armed war in their country. Conflict is a significant stress and social determinant of children's health. In the statements within this data scope, much of the data review available knowledge about the impact of armed conflict on children and support the recommendations in the accompanying Policy Statement on children and armed conflict. Future research needs to use scientific articles sourced from other reputable international databases, such as the Web of Science and Dimensions Scholars.